Optimal sizing of compensating capacitor in distribution system using Artificial Immune System (AIS) - Mohd Izhar Mohd Said (School of Electrical Systems Engineering, 2009)
Compensating capacitor is one of the method that used by engineers to reduce power losses. This project has been done to make the finding of the suitable value for capacitor in distribution system easier. Technique that used to find the optimal size is the artificial immune system (AIS). Newton-Raphson methods were used for the power flow solution. For the project test system, it is used for the 6-bus system. This project was done by using MATLAB software. The software can do much kind of work, example like mathematical calculation, image processing, system analyzing, write programmed and many more.